Energy Technology 2019 Carbon Dioxide Management and Other Technologies - Wang, Tao; Chen, Xiaobo; Guillen, Donna Post; Zhang, Lei; Sun, Ziqi; Wang, Cong; Haque, Nawshad; Howarter, John A.; Neelameggham, Neale R.; Ikhmayies, Shadia; Smith, York R.; Tafaghodi, L.; et al. (The Minerals, Metals & Materials Series,, 2019)
This collection addresses the need for sustainable technologies with reduced energy consumption and pollutants and the development and application of alternative sustainable energy to maintain a green environment and energy supply. Contributions focus on energy-efficient technologies including innovative ore beneficiation, smelting technologies, and recycling and waste heat recovery, as well as emerging novel energy technologies. Papers also cover various technological aspects of sustainable energy ecosystems, processes that improve energy efficiency, reduce thermal emissions, and reduce carbon dioxide and other greenhouse emissions. Papers from the following symposia are presented in the book: Energy Technologies and Carbon Dioxide Management Solar Cell Silicon Advanced Materials for Energy Conversion and Storage .